Cinza vegetal e disponibilidades hídricas na cultura do feijão-mungo-verde em latossolo vermelho do Cerrado - Dourado, Luana Glaup Araujo (2020)
The Brazilian Cerrado is characterized by irregular rainfall, with symptoms of weathered soil, low natural fertility and high acidity. Due to the low pH, several nutrients are found unavailable in the soil, and available from the correction of your acidity. A proposal in this scenario is the addition of agro-industrial wastes to the soil (wood ash) as potential sources of correctives and nutrients, because it is presented as a material with strong neutralizing power and with significant amounts of macro and micronutrients, as well as its potential to increase water retention in the soil and therefore its availability for crops during the dry season. The definition of the amount of water to be applied at the time of irrigation, such as, for example, the establishment of nutrient doses for plants, makes production economically viable, with a significant increase in growth, development and crop production, with consequent maximization of profits. In Cerrado soils, the green mung bean (Vigna radiata L.) is an excellent legume option for agricultural grown which, due to its rapid growth, his short production cycle and her adaptation to tropical and subtropical climates, is one of the growing options for -season species and as the main crop for small farmers. In this context, the objective of this experiment was to obtain the effect of different doses of wood ash and the availability of water in the growth of green mung bean in Oxisol from Cerrado. The experiment was carried out in a greenhouse, using a completely randomized block design in a 5x5 factorial schem, corresponding to five doses of wood ash (0; 8; 16; 24 and 32 g dm-3) and five water tensions in the soil (4, 8, 16, 32 and 64 kPa), with four replicates. The evaluations were carried out at 15, 30, 45 and 60 days after the emergence of the plants, with the following variables: plant height, number of leaves, stem diameter and chlorophyll index; and at the time of cutting: leaf area, number of pods, number of grains, dry mass of grains, dry mass of shoots and roots, root volume, number and dry mass of nodules, harvest index and efficiency in the use of water by the crop, in addition to chemical soil analysis (pH, P, K, Ca, Mg, Al, CTC, M.O and V%). The response variables were subjected to analysis of variance and regression test, both with up to 5% probability of error, using the SISVAR statistical program. Wood ash doses between 24 and 29 g dm-3 and a tension of 4 kPa promote the best responses to the morphological and yield variables of mung bean plants. The incorporation of the wood ash into the soil increases the pH and the availability of nutrients. In this way, the wood ash and the humidity close to the field capacity provide the best results for the yield of green mung beans growth in Oxisol of the Cerrado.